DIRECTIONS OF ATTRACTING DEPOSIT FUNDS AS THE MAIN SOURCE OF INVESTMENT OF INDEPENDENT BUSINESS - Melnychuk , Yu.M.; Chvertko, L.A. (The actual problems of regional economy development, 2021)
The deposits involved are the foundation on which banks develop and succeed. The ability to raise a significant amount of funds shows the professionalism of management and high confidence in the bank from the client's side. The article "Directions of attracting deposits as the main source of investment for independent business" is aimed at studying the bank's deposit operations as a valuable source of investment for small and medium-sized businesses in Ukraine, to create an independent climate for their activities. The purpose of the article is to explore the basic provisions of the mechanism of providing deposit obedience to the bank and ways to improve them for further accumulation in investment flows for small, medium and large enterprises. The set of research methods was used in the work, which is the methodology of analysis and organization of major publications, legislation and laws, namely the methods of generalization, comparison, chronology, analysis and generalization. The article considers that the main source of deposits is the population's deposits. In addition to private investors, corporate clients play a special role. The problems of the deposit policy of Ukrainian banks at the present stage are revealed and the ways of their solution are offered. It is proved that for the bank the tendency to reduce the volume of household deposits and deposits of enterprises and organizations is the most acute problem, forcing it to reconsider its deposit policy, so the proposed ways to attract depositors to banks. The most invested sectors of the economy with bank deposits are analyzed. The results of the study were the conclusions made on the basis of a study of the scientific and legal framework on this issue, as well as the analysis of raising funds in deposits and deposits of individuals and legal entities; improving the resource base through the proposed ways of receiving deposit flows. The practical significance of the research and its results are the proposed ways to improve the process of attracting cash flows to bank deposits for investment potential.